Recommendations for the meanings of words by Estonian language planning – justified and necessary, or not? - Risberg , Lydia (Taikomoji kalbotyra, 2023)
On the example of Estonian language planning, this research paper explores whether it is justified and necessary to give recommendations for the meanings of words. The focus is on the general language. Technical language is out of the scope of this research. First, a brief overview of the history of Estonian language planning and the development of Standard Estonian, as well as the current situation is provided. Then the paper focuses on recent research on the meanings of words in Estonian. The purpose was to revise the recommendations for the meanings of words by Estonian language planning. The research is based on the common approaches in Estonian linguistics today – the usage-based linguistics and corpus linguistics. The paper argues that recommendations by language planning for the meanings of words are not justified nor necessary in the general language, even if some explanations on the choice of words are relevant (e.g., for offensive words).